The magic trap - Davies, Jacqueline, 1962- (Davies, Jacqueline, 1962- Lemonade war series, 2014)
"A magic show, card tricks, and a disappearing rabbit named Professor Hoffman--the Treski kids are at it again as they try to put on a show in the face of an approaching hurricane. But nothing prepares them for what blows into town next: their long-lost dad"--